Plastic responses to hot temperatures homogenize riparian leaf litter, speed decomposition, and reduce detritivores. Issue 10 (8th August 2021) - Jeplawy, Joann R.; Cooper, Hillary F.; Marks, Jane; Lindroth, Richard L.; Andrews, Morgan I.; Compson, Zacchaeus G.; Gehring, Catherine; Hultine, Kevin R.; Grady, Kevin; Whitham, Thomas G.; Allan, Gerard J.; Best, Rebecca J.
Abstract: Efforts to maintain the function of critical ecosystems under climate change often begin with foundation species. In the southwestern United States, cottonwood trees support diverse communities in riparian ecosystems that are threatened by rising temperatures. Genetic variation within cottonwoods shapes communities and ecosystems, but these effects may be modified by phenotypic plasticity, where genotype traits change in response to environmental conditions. Here, we investigated plasticity in Fremont cottonwood ( Populus fremontii ) leaf litter traits as well as the consequences of plasticity for riparian ecosystems. We used three common gardens each planted with genotypes from six genetically divergent populations spanning a 12°C temperature gradient, and a decomposition experiment in a common stream environment. We found that leaf litter area, specific leaf area, and carbon to nitrogen ratio (C:N) were determined by interactions between genetics and growing environment, as was the subsequent rate of litter decomposition. Most of the genetic variation in leaf litter traits appeared among rather than within source populations with distinct climate histories. Source populations from hotter climates generally produced litter that decomposed more quickly, but plasticity varied the magnitude of this effect. We also found that hotter growing conditions reduced the variation in litter traits produced across genotypes, homogenizing the litter inputs to riparian ecosystems. All genotypes in the hottest garden produced comparatively small leaves that decomposed quickly and supported lower abundances of aquatic invertebrates, whereas the same genotypes in the coldest garden produced litter with distinct morphologies and decomposition rates. Our results suggest that plastic responses to climate stress may constrict the expression of genetic variation in predictable ways that impact communities and ecosystems. Understanding these interactions between genetic and environmental variation is critical to our ability to plan for the role of foundation species when managing and restoring riparian ecosystems in a warming world.